Wacana Khitan Perempuan Di Masyarakat Desa (Studi Di Masyarakat Desa Pager, Kecamatan Purwosari, Kabupaten Pasuruan) - Nashichuddin, Ach. (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2003)
This research aims to describe a discourse of female circumcision in Pager village, Purwosari district, Pasuruan. There are two discourses that are described in this research; discourse of fiqh text that consists of books written by Moslem scholar of Syafi'iyah and discourse of social context in the village. This research found that no all fiqh books, which are spread over in society explain about female circumcision. The explanation is only found in advanced fiqih books that seldom be touched by civil society. In fiqh books expressed that majority of Moslem scholar see that female circumcision is religious obligatory either for men and woman. For a while other minority Moslem scholar see that it is obliged to men and recommended to woman. There is a significant difference between the fiqih text and the social context in Pager in explaining the meaning of female circumcision practice. There are three factors that cause the difference; the social and cultural change in the society, the change of thought system in the society, and the lack of knowledge regarding the fiqih text that explains female circumcision.